2019
DOI: 10.1002/rcm.8424
|View full text |Cite
|
Sign up to set email alerts
|

A nanoparticle co‐matrix for multiple charging in matrix‐assisted laser desorption ionization imaging of tissue

Abstract: Rationale A two‐component matrix of 2‐nitrophloroglucinol (2‐NPG) and silica nanoparticles was used for matrix‐assisted laser desorption ionization (MALDI) mass spectrometry imaging of high‐charge‐state biomolecules in tissue. Potential advantages include increased effective mass range and efficiency of fragmentation. Methods A mixture of 2‐NPG matrix and silica nanoparticles was applied to cyrosectioned 10 μm thick mouse brain tissue. The mixture was pipetted onto the tissue for profiling and sprayed for tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Wang et al, 2015;C. Zhao, Li, et al, 2018) 4-Phenyl-α-cyanocinnamic acid amide Negative Lipids (Fülöp et al, 2013) 2-Nitrophloroglucinol (2-NPG) Positive Proteins (Banstola & Murray, 2021) Silver nanoparticles (AgNPs) Positive Lipids (Guan et al, 2018) N-and P-doped graphene Positive/negative Metabolites (H. Zhao, Li, et al, 2018) Graphene oxide (GO) Negative Lipids (D. to range from 17.2% to 35.9% (Ly et al, 2019). Efforts have been made to improve the site-to-site reproducibility of MALDI MSI experiments (Boskamp et al, 2021).…”
Section: -Mercaptobenzothiazole (Mbt)mentioning
confidence: 99%
“…Wang et al, 2015;C. Zhao, Li, et al, 2018) 4-Phenyl-α-cyanocinnamic acid amide Negative Lipids (Fülöp et al, 2013) 2-Nitrophloroglucinol (2-NPG) Positive Proteins (Banstola & Murray, 2021) Silver nanoparticles (AgNPs) Positive Lipids (Guan et al, 2018) N-and P-doped graphene Positive/negative Metabolites (H. Zhao, Li, et al, 2018) Graphene oxide (GO) Negative Lipids (D. to range from 17.2% to 35.9% (Ly et al, 2019). Efforts have been made to improve the site-to-site reproducibility of MALDI MSI experiments (Boskamp et al, 2021).…”
Section: -Mercaptobenzothiazole (Mbt)mentioning
confidence: 99%
“…9,[25][26][27] A recent study also reported that multiply charged protein ions were detected with high sensitivity in MALDI imaging analysis using a mixture of 2-NPG matrix and silica nanoparticles. 28 However, due to the nature of the 2-NPG matrix used to form crystal needles, 29 heterogeneous sample distributions are easily formed, resulting in poor reproducibility. Therefore, in the current study, we applied the FDD method and a 2-NPG matrix to improve homogeneity and detect highly multiply charged ions of proteins such as cytochrome c, myoglobin, and IgG.…”
Section: Introductionmentioning
confidence: 99%
“…77 Murray's group (Louisiana State University, Baton Rouge, LA, USA) measured particle sizes after laser ablation of LSI and other matrices, 78,79 introduced a pulsed valve ionization method in which one of the MAI matrices is knocked off a surface in close proximity to the heated mass spectrometer inlet, 80 and used MAI matrices as co-matrix for tissue analyses. 81 Halvorsen et al (University of Oslo, Oslo, Norway) demonstrated the utility of single reaction monitoring for quantitative proteomics using MAI on a triple quadrupole mass spectrometer. 82 Methods which may fully or in part utilize the novel mechanism of ionization have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Rybkin et al (Institute of Problems of Chemical Physics, Chernogolovka, Russia) modified the MAI approach by guiding the matrix:analyte sample on a wire into the sub‐AP region of the mass spectrometer where the ionization proceeds to characterize dyes 77 . Murray's group (Louisiana State University, Baton Rouge, LA, USA) measured particle sizes after laser ablation of LSI and other matrices, 78,79 introduced a pulsed valve ionization method in which one of the MAI matrices is knocked off a surface in close proximity to the heated mass spectrometer inlet, 80 and used MAI matrices as co‐matrix for tissue analyses 81 . Halvorsen et al (University of Oslo, Oslo, Norway) demonstrated the utility of single reaction monitoring for quantitative proteomics using MAI on a triple quadrupole mass spectrometer 82 …”
Section: Introductionmentioning
confidence: 99%